IEC and CENELEC standards used to protect the electrical worker against an Arc Flash - Bardet, Nicolas (2017 12th International Conference on Live Maintenance (ICOLIM), 2017)
In the field of Standards, regulations and legal aspects it is important to underline the use of IEC and CENELEC standards used to protect the electrical worker against an Arc Flash. This presentation gives a practical overview of the standardization on the subject.